Using the MMPI-2-RF, IOP-29, IOP-M, and FIT in the In-Person and Remote Administration Formats: A Simulation Study on Feigned mTBI. - Giromini, Luciano; Pignolo, Claudia; Zennaro, Alessandro; Sellbom, Martin (Assessment, 2024)
Our study compared the impact of administering Symptom Validity Tests (SVTs) and Performance Validity Tests (PVTs) in in-person versus remote formats and assessed different approaches to combining validity test results. Using the MMPI-2-RF, IOP-29, IOP-M, and FIT, we assessed 164 adults, with half instructed to feign mild traumatic brain injury (mTBI) and half to respond honestly. Within each subgroup, half completed the tests in person, and the other half completed them online via videoconferencing. Results from 2 ×2 analyses of variance showed no significant effects of administration format on SVT and PVT scores. When comparing feigners to controls, the MMPI-2-RF RBS exhibited the largest effect size (d = 3.05) among all examined measures. Accordingly, we conducted a series of two-step hierarchical logistic regression models by entering the MMPI-2-RF RBS first, followed by each other SVT and PVT individually. We found that the IOP-29 and IOP-M were the only measures that yielded incremental validity beyond the effects of the MMPI-2-RF RBS in predicting group membership. Taken together, these findings suggest that administering these SVTs and PVTs in-person or remotely yields similar results, and the combination of MMPI and IOP indexes might be particularly effective in identifying feigned mTBI.